Fear of missing out (FoMO) among social media users: a systematic literature review, synthesis and framework for future research. Issue 3 (12th February 2021) - Tandon, Anushree; Dhir, Amandeep; Almugren, Intesar; AlNemer, Ghada Naif; Mäntymäki, Matti
Abstract : Purpose: Research examining the "fear of missing out" (FoMO) is increasingly prominent, with a growing number of studies exploring this phenomenon. Despite the increased academic interest, no attempts have been made to synthesize extant knowledge on FoMO. There is limited holistic understanding of its conceptualization and operationalization. To address this gap, an exhaustive systematic literature review (SLR) on FoMO is presented. Design/methodology/approach: Systematic review protocols and content analysis was used to analyze and synthesize insights from 58 empirical studies obtained from four academic databases: Scopus, Web of Science, PubMed and PsycINFO. Findings: Significant diversity in prior research on FoMO was encapsulated in four themes. There are significant limitations in conceptualization of FoMO, along with narrow focus on geographic, methodological and contextual foci of prior studies. The authors propose a comprehensive framework and extensive gap-specific research directions to aid future research. Research limitations/implications: The SLR is limited in its consideration of empirical studies published in academic journal articles obtained from four databases. Social implications: The authors imply the critical need to ascertain motives for individuals' excessive engagement with social media and the subsequent impact on well-being indicators (e.g. sleep quality) and functional impairments (e.g. addiction). Originality/value: This study magnifies and expands the intellectual boundaries of FoMO and suggests the adoption of a multidisciplinary perspective for further investigation. The use of novel theoretical lenses can further ascertain FoMO's effect on different cultures and social media users.